Case Report: Resolution of Lichen Planus Pemphigoides as an unexpected outcome of SARS-CoV-2 infection - Ruffo di Calabria, Valentina; Verdelli, Alice; Quintarelli, Lavinia; Corrà, Alberto; Mariotti, Elena Biancamaria; Aimo, Cristina; Del Bianco, Elena; Bianchi, Beatrice; Maio, Vincenza; Massi, Daniela; Caproni, Marzia (Frontiers in Immunology, 2023)
It is well known that viral infections play a relevant role in inducing or protecting from autoimmune diseases, thus representing a major environmental factor in the disruption of the immune system in genetically susceptible individuals. Since the beginning of the Covid-19 pandemic a great number of clinical and epidemiological studies have demonstrated that SARS-CoV-2 infection is no exception to the rule by interfering on many different levels in the normal functioning of our immune system. Even though a growing number of case series and case reports has been cited in the literature linking the infection to the new onset of autoimmune diseases, to date very little has been reported concerning a possible correlation between the virus and the clinical resolution of any kind of autoimmune pathology. Here we describe an interesting case of abrupt and unexpected resolution of Lichen planus pemphigoides mucocutaneous lesions in a fully vaccinated patient after a mildly symptomatic SARS-CoV-2 respiratory infection and we speculate on the possible underlying mechanisms correlating the two events.